Does water quality matter? Foraging activity of Daubenton’s bat (Myotis daubentonii) over three lakes with different trophy - Małgorzata Strzałka; Katarzyna Kozakiewicz; Postawa Tomasz (Theriologia Ukrainica)
The trophic parameters of water bodies, especially the content of biogenic components, may have an impact on invertebrate communities, both those strictly aquatic and those using the water bodies periodically. Among this group, insects are highly relevant, the density of which can affect the attractiveness of the water body as foraging habitat of water-surface forager bats. The present paper presents the results of a study measuring the foraging activity of Myotis daubentonii (Kuhl, 1917) in linear transects over three water bodies: an oligotrophic, eutrophic, and dystrophic lake located within a 1.5 km radius. The research has a repeated measures design, with the consecutive surveys carried out in 1995, 1996, and 2001 in the lactation period (end of June–beginning of July) and in the post-lactation period (end of August–beginning of September). The activity of M. daubentonii over the oligotrophic lake varied between 0.0 and 15.9 ind/km, while over the eutrophic lake it was 3.9 and 16.7 ind/km, and over the dystrophic lake was 3.4 and 30.5 ind/km. The study found that the foraging activity above the dystrophic lake was almost twice as high (13.1 ± 6.11) as over the two others lakes: oligotrophic (6.0 ± 4.17) and eutrophic (8.0 ± 3.19). By contrast, in the case of M. daubentonii, there was no statistically significant difference in the foraging activity over either of the foraging areas (eutrophic and oligotrophic). The foraging activity in bats in the lactation period was higher than in the post-lactation period. Our results indicate that the differences in the foraging activity of the bats in the present study do not depend on the trophic status of the lake and are linked directly to opportunistic foraging strategy of the species. The higher foraging activity recorded over the small dystrophic lake may be explained by the isolation of this lake from adverse weather conditions (e.g. wind). Hence, the observed slow increase in the number of M. daubentonii over the past 20 years cannot be attributed to, as previously suggested, eutrophication, but, on the contrary, seems to be a result of a progressive improvement in the environment.